2010
DOI: 10.1377/hlthaff.2009.0709
|View full text |Cite
|
Sign up to set email alerts
|

Adopting A Surgical Safety Checklist Could Save Money And Improve The Quality Of Care In U.S. Hospitals

Abstract: Use of the World Health Organization’s Surgical Safety Checklist has been associated with a significant reduction in major post-operative complications after inpatient surgery. We hypothesized that implementation in the United States would be cost saving at the hospital level. We performed a decision analysis comparing implementation of the checklist to existing practice in American hospitals. In a hospital with a baseline major complication rate after surgery of at least 3%, the checklist is cost saving once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 20 publications
1
101
0
7
Order By: Relevance
“…3,4,5,6,7,8 In our study we had tried to analyse the awareness status about the safety checklist in our region. Unfortunately the majority of the surgeons in our study were found not to be aware properly about the checklist and are currently not using the checklist in their practice.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,5,6,7,8 In our study we had tried to analyse the awareness status about the safety checklist in our region. Unfortunately the majority of the surgeons in our study were found not to be aware properly about the checklist and are currently not using the checklist in their practice.…”
Section: Resultsmentioning
confidence: 99%
“…In neurosurgery a simple wound infection may lead to multiple reoperations and long antibiotic treatments, and hence cause greater costs than infections in other surgical specialties. 15,25 The use of a surgical checklist is simple and inexpensive, and could indirectly save money, 18 redundant work, and suffer ing of patients. There is a need for surgical checklists in all types of surgery, 13 but especially in neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…70,406,551,552 Empirical research supports assertions that the WHOSSC (i) saves lives; [553][554][555][556][557] (ii) improves communication across the surgical team; 558 (iii) reduces the occurrence of wrong-site surgery; 63 (iv) promotes adherence to defined antibiotic protocols, thereby reducing the incidence of surgical-site infection; [559][560][561] and (v) fosters more efficient use of theatre time and resources, 556 while supporting appropriate staffing levels. 439 Despite such obvious benefits, operationalisation of the WHOSSC may be poor.…”
Section: Reducing Surgical Complicationsmentioning
confidence: 98%